Hepatic Mitochondrial Damage Aggravated By Azathioprine: Protective Effect of Quercetin - meenu shrivastava; S Nayak; Shobhit Shrivastava (International Journal of Phytomedicine, 2013)
Mitochondrian play an important role in the production of energy and cell cycle regulation. Administration of azathioprine (AZA), an immunosuppressant drug, adversely affects the hepatic mitochondria which may culminate hepatotoxicity. The present study was undertaken to evaluate the effect of quercetin (QE), against AZA induced hepatic injury in Wistar rats. AZA (50 mg/kg body weight, i.p.) was administered once on the 7th day of experiment. A significant depletion in the levels of manganese superoxide dismutase (MnSOD), glutathione peroxidase (GPx) and reduced glutathione (GSH) were observed in AZA alone treated rats. Simultaneous decrease in the levels of tricarboxylic acid (TCA) enzymes such as isocitrate dehydrogenase (ICDH), α-ketoglutarate dehydrogenase (α-KGDH ), succinate dehydrogenase (SDH) and malate dehydrogenase (MDH) were observed. Decrease in the levels of these enzymes suggests a loss in mitochondrial function and integrity. Lipids existing in the mitochondrial membrane were peroxidised, and measured by the production of malondialdehyde (MDA). The supplementation of QE (50mg/kg body weight) restored the depleted levels of enzymes and above hepatic mitochondrial abnormality to near normalcy. The present study highlights the antioxidant property of QE in improving the mitochondrial functions in AZA induced hepatic degradation